Use of fibrates is not associated with reduced risks of mortality or cardiovascular events among ESRD patients: A national cohort study - Ho, Wen-Yu; Yen, Chieh-Li; Lee, Cheng-Chia; Tu, Yi-Ran; Chen, Chao-Yu; Hsiao, Ching-Chung; Chu, Pao-Hsien; Hsu, Hsiang-Hao; Tian, Ya-Chun; Chang, Chih-Hsiang (Frontiers in Cardiovascular Medicine, 2022)
Background Although a recent study reported that fibrates are associated with a low risk of cardiovascular (CV) death and can postpone the need for long-term hemodialysis in patients with advanced chronic kidney disease (CKD), little is known regarding whether the CV protective effects of fibrates extend to patients with end-stage renal disease (ESRD). The present study compared CV outcomes and mortality among patients with ESRD treated with fibrates, statins, neither, or their combination. Methods This cohort study extracted data from Taiwan's National Health Insurance Research Database (NHIRD). Adult patients with ESRD and hyperlipidemia were identified and categorized into four groups (fibrate, statin, combination, and non-user groups) according to their use of different lipid-lowering therapies within 3 months prior to the commencement of permanent dialysis. Inverse probability of treatment weighting was used to balance the baseline characteristics of the groups. The follow-up outcomes were all-cause mortality, CV death, and major adverse cardiac and cerebrovascular events (MACCEs). Results Compared with the non-user and statin groups, the fibrate group did not exhibit significantly lower risks of all-cause mortality [fibrate vs. non-user: hazard ratio (HR), 0.97; 95% confidence interval (CI), 0.92–1.03; statin vs. fibrate: HR, 0.95; 95% CI, 0.90–1.01], CV death (fibrate vs. non-user: HR, 0.97; 95% CI, 0.90–1.05; statin vs. fibrate: HR, 0.97; 95% CI, 0.90–1.06), and MACCEs (fibrate vs. non-user: HR, 1.03; 95% CI, 0.96–1.10; statin vs. fibrate: HR, 0.94; 95% CI, 0.87–1.004). The combination of fibrates and statins (specifically moderate- to high-potency statins) did not result in lower risks of all-cause mortality, CV death, or MACCEs compared with statins alone. Conclusion In patients with ESRD, the use of fibrates might be not associated with reduced mortality or CV risks, regardless of whether they are used alone or in combination with statins.